2021
DOI: 10.1016/j.cpcardiol.2020.100746
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Air Travel for Passengers With Cardiovascular Disease: Stressors of Flight and Aeromedical Impact

Abstract: The exponential growth of commercial flights has resulted in a sharp rise of air travellers over the last 2 decades, including passengers with a wide range of cardiovascular conditions. Notwithstanding the ongoing COVID-19 pandemic that had set back the aviation industry for the next 1 to 2 years, air travel is expected to rebound fully by 2023-2024. Guidelines and evidence-based recommendations for safe air travel in this group vary, and physicians often encounter situations where opinions and assessments on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
(91 reference statements)
0
2
0
1
Order By: Relevance
“…Previous studies have reported that aeromedical evacuation involves different types of aircraft, including commercial and charter aircraft and helicopters. This diversity of transport modes contributes to other experiences in providing patient care during the flight (Imbriaco et al, 2021 ; Koh, 2021 ; Thomson, 2015 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have reported that aeromedical evacuation involves different types of aircraft, including commercial and charter aircraft and helicopters. This diversity of transport modes contributes to other experiences in providing patient care during the flight (Imbriaco et al, 2021 ; Koh, 2021 ; Thomson, 2015 ).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, nurses must be able to intervene despite the many constraints in the aircraft. The aviation environment presents a considerable number of challenges and limitations, especially in the provision of nursing care, which include changes in air pressure, temperature fluctuations, hypoxia, gravitational forces during take-off and landing, air humidity, noise, vibration, turbulence, limited space, and inadequate lighting (Butler et al, 2018 ; Koh, 2021 ; Thomson, 2015 ). Limited space that constrains access to the patient while in flight may limit treatment capabilities (Thibeault & Evans, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tekanan parsial adalah tekanan yang dihasilkan oleh masing-masing gas jika gas tersebut memenuhi volume atau ruang yang ditempati oleh beberapa jenis gas pada suhu yang sama. 5,6 Kondisi lingkungan kabin selama penerbangan berbeda dengan kondisi normal di darat; ditandai dengan berkurangnya tekanan parsial oksigen dan kelembapan lebih rendah, distribusi udara yang tidak merata di dalam kabin, dan persentase udara yang didaur ulang di dalam lingkungan pesawat. Selama penerbangan, kabin merupakan lingkungan tertutup berventilasi yang dikendalikan oleh sistem kontrol lingkungan (environmental control system) untuk menjaga tekanan udara yang nyaman di dalam kabin pesawat.…”
Section: Pendahuluanunclassified